2017
DOI: 10.1038/s41598-017-12172-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of DNA unlinking: A story of stepwise simplification

Abstract: In Escherichia coli DNA replication yields interlinked chromosomes. Controlling topological changes associated with replication and returning the newly replicated chromosomes to an unlinked monomeric state is essential to cell survival. In the absence of the topoisomerase topoIV, the site-specific recombination complex XerCD- dif-FtsK can remove replication links by local reconnection. We previously showed mathematically that there is a unique minimal pathway of unlinking replication links by reconnection whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 41 publications
1
45
0
1
Order By: Relevance
“…The same research group later showed that the XerCD-dif -FtsK enzymatic complex could unlink replication links tied in vivo in E. coli cells deficient in the decatenase topoIV [33]. Several groups of authors, including our own, studied mathematically the mechanism and pathways of DNA unlinking by site-specific recombination [12,13,83,85]. In [83] we showed that at least 2m steps are needed to unlink a replication link of type T (2, 2n) with one recombination site in each component in the orientation indicated in Figure 3.…”
Section: 3mentioning
confidence: 98%
See 2 more Smart Citations
“…The same research group later showed that the XerCD-dif -FtsK enzymatic complex could unlink replication links tied in vivo in E. coli cells deficient in the decatenase topoIV [33]. Several groups of authors, including our own, studied mathematically the mechanism and pathways of DNA unlinking by site-specific recombination [12,13,83,85]. In [83] we showed that at least 2m steps are needed to unlink a replication link of type T (2, 2n) with one recombination site in each component in the orientation indicated in Figure 3.…”
Section: 3mentioning
confidence: 98%
“…Each reconnection represented a non-coherent banding. The implementation was adapted from our published work in [85] (see Section 5.3 for more details). Table 1.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…It is often convenient to isotope L 1 and L 2 so that a coherent or non-coherent band surgery can be expressed as the replacement of a rational (0) tangle by an (∞) or (±1/n) tangle ( Figure 9). When n is small, these tangles have special relevance in biology (see for example [69,71,70,64,67]). For example, in the context of DNA recombination, the local reconnection sites correspond to the core regions of the recombination sites, i.e.…”
Section: Relevance Of Theorem 11 and Corollary 12 To Dna Topologymentioning
confidence: 99%
“…If the linking number is instead −n/2, Corollary 1.2 follows from the characterization of coherent band surgeries between T (2, n) torus links and certain two-bridge knots in [21,Theorem 3.1]. While both coherent and non-coherent band surgeries have biological relevance, more attention in the literature has been paid to the coherent band surgery model (see for example [37,21,64,38,13,14,67]). This is due in part to the relative difficulty in working with non-orientable surfaces, as is the case with non-coherent band surgery on knots.…”
Section: Introductionmentioning
confidence: 99%